2021
DOI: 10.1007/s10691-021-09465-3
|View full text |Cite
|
Sign up to set email alerts
|

Rupture and Continuity: Abortion, the Medical Profession, and the Transitional State—A Polish Case Study

Abstract: Taking Poland as a case study, this article examines the sociological and historical-institutional factors that determine the relationship between the process of medical professionalisation and reproductive rights in transitional societies. Focusing on three periods in Polish history, (a) Partition era (1772–1918), (b) the Second Polish Republic (1918–1939), and (c) the post-war period (1945–1989), it identifies ruptures and continuities that have shaped the development of the Polish medical profession and its… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 72 publications
0
11
0
Order By: Relevance
“…The second National Assembly of Physicians adopted the first Medical Code of Ethics in 1991 without prior consultation with the members of the medical profession, except for those who were already anti-choice (Hoff, 1994: 632). As argued elsewhere, this was possible because the main organs of the Chambers have been dominated by doctors active in the Solidarity movement in the 1980s and closely linked to the Catholic Church (Krajewska, 2021). Through these connections, the main medical professional body in Poland after 1989 became a powerful ally of the Catholic Church and an active supporter of its anti-abortion agenda.…”
Section: Legal Institutional and Professional Factors Shaping Medical...mentioning
confidence: 98%
See 1 more Smart Citation
“…The second National Assembly of Physicians adopted the first Medical Code of Ethics in 1991 without prior consultation with the members of the medical profession, except for those who were already anti-choice (Hoff, 1994: 632). As argued elsewhere, this was possible because the main organs of the Chambers have been dominated by doctors active in the Solidarity movement in the 1980s and closely linked to the Catholic Church (Krajewska, 2021). Through these connections, the main medical professional body in Poland after 1989 became a powerful ally of the Catholic Church and an active supporter of its anti-abortion agenda.…”
Section: Legal Institutional and Professional Factors Shaping Medical...mentioning
confidence: 98%
“…Another, complementary and perhaps more plausible, explanation of the Chamber's ambivalent stance towards abortion would be that while professional bodies influence the construction of the regulatory environment in which other healthcare institutions operate, they themselves do not operate in an institutional vacuum. What can be observed in Poland is a unique symbiosis of the state, the professions and healthcare institutions, which for decades has perpetuated and reinforced very particular individual and collective behaviour with regard to abortion (Krajewska 2021). It is this symbiosis that facilitated the deep influence of the Catholic Church on abortion practice.…”
Section: The Role Of Professional Bodies In the Construction Of Legal...mentioning
confidence: 99%
“…Critical Junctures and Legacies of Rupture. Adelman (1998), della Porta (2020), and Krajewska (2021) all theorized rupture in the context of critical junctures. Della Porta (2020) described rupture as "processes of cracking, as the production of sudden ruptures; vibrating, as contingently reproducing those ruptures; and sedimenting, as the stabilization of the legacy of the rupture" (p. 556).…”
Section: Analysis Of the Researchmentioning
confidence: 99%
“…According to Krajewska, ruptures and continuities over three historical time periods have influenced the medical profession in Poland and attitudes toward abortion. Krajewska's (2021) case study demonstrated that "when systemic changes take place, some institutions remain dormant or suspended. Values embedded in these institutions may become latent but they never fully disappear" (pp.…”
Section: Analysis Of the Researchmentioning
confidence: 99%
See 1 more Smart Citation